SOME STATISTICAL PICTURE OF MAGNETIC CP STARS EVOLUTION - Gopka, V. F.; Ulyanov, O. M.; Andrievsky, S. M.; Shavrina, S. A.; Yushchenko, V. A. (Одеські астрономічні публікації, 2010)
We discuss some statistical results on the evolution of magnetic CP stars in the framework of the supposition about their binary nature.